Liquid-gas boundary catalysis by gold/polystyrene-coated hollow titania and the effective location of active sites in liquid-liquid phase-boundary catalyst [electronic resource] - Nur Hidayah Mohd. Ran, 1987-, author 500382; Hadi Nur, supervisor 378090; Lee, Siew Ling supervisor 546175; Leny Yuliati, supervisor 632194; Fakulti Sains 8004 (2014)
Thesis (Ph.D (Kimia)) - Universiti Teknologi Malaysia, 2014